Hippocampal-neocortical interactions in memory formation, consolidation, and reconsolidation.[article]. - Wang, Szu-Han
This review,focusing on work using animals, updates the approach whose aim is to translate neuropsychological ideas about the psychological and anatomical organization of memory into the neurobiological domain. It is suggested that episodic-like memory consists of both automatic and controlled components, with the medial temporal mediation of memory encoding including the neurobiological mechanisms that are primarily automatic or incidental. These ideas, in the cognitive and behavioral domain, are linked to neurophysiological ideas about cellular consolidation concerning synaptin potentiation, particularly the relation between protein synthesis-dependent long-term changes ans shorter-lasting post-translational mechanisms. Ideas fron psychology about mental schemas are considered in relation to the phenomenon of systems consolidation and, specifically, about how prior knowledge can alter the rate at which consolidation occurs. Finally, the hippocampal-neocortical interactions theory is updated in relation to reconsolidation, a process the enables updating of stored memory traces in response to novelty.